Co-expression of vasopressin and androgen-binding protein in the rat hypothalamus - Jirikowski, Gustav F.; Herbert, Zsófia; Petrusz, Peter; Sendemir, Erdogan; Caldwell, Jack D. (Journal of chemical neuroanatomy, 2005)
In previous studies we have observed the expression of androgen binding protein (ABP) in the rat hypothalamo-neurohypophysial system. With immunocytochemical double staining we found partial co-localization with oxytocin. In the present study we used antibodies to the anti-diuretic hormone arginine vasopressin (AVP) for co-localization with ABP in the rat hypothalamus. Both antigens were seen in the magnocellular paraventricular and supraoptic nuclei. Dense fiber networks with varicosities containing both AVP and ABP immunoreactivity were visible throughout the hypothalamus, the median eminence and in the posterior pituitary lobe. Double immunostaining revealed also co-existence in the parvocellular portion of the paraventricular nucleus and in the suprachiasmatic nucleus. ABP immunoreactive neurons in the preoptic region were devoid of AVP staining, AVP neurons in the bed nucleus of the stria terminalis stained only occasionally for ABP. We conclude that both the magnocellular and the parvocellular hypothalamic vasopressin systems are capable of expressing the steroid binding globulin, which is probably subject to axonal transport, along with the peptide hormone. Intrahypothalamic expression of ABP may be among the mechanisms necessary for rapid actions of steroids on hypothalamic neuroendocrine systems.